Night-shift work and breast cancer - a systematic review and meta-analysis - Sharea Ijaz; Jos Verbeek; Andreas Seidler; Marja-Liisa Lindbohm; Anneli Ojajärvi; Nicola Orsini; Giovanni Costa; Kaisa Neuvonen (Nordic Association of Occupational Safety and Health (NOROSH), 2013)
OBJECTIVE: The aim of this review was to synthesize the evidence on the potential relationship between nightshift work and breast cancer. METHODS: We searched multiple databases for studies comparing women in shift work to those with no-shift work reporting incidence of breast cancer. We calculated incremental risk ratios (RR) per five years of night-shift work and per 300 night shift increases in exposure and combined these in a random effects dose-response meta-analysis. We assessed study quality in ten domains of bias. Results We identified 16 studies: 12 case-control and 4 cohort studies. There was a 9% risk increase per five years of night-shift work exposure in case-control studies [RR 1.09, 95% confidence interval (95% CI) 1.02-1.20; I^2=37%, 9 studies], but not in cohort studies (RR 1.01, 95% CI 0.97-1.05; I^2 =53%, 3 studies). Heterogeneity was significant overall (I^2=55%, 12 studies). Results for 300 night shifts were similar (RR 1.04, 95% CI 1.00-1.10; I^2=58%, 8 studies). Sensitivity analysis using exposure transformations such as cubic splines, a fixed-effect model, or including only better quality studies did not change the results. None of the 16 studies had a low risk of bias, and 6 studies had a moderate risk. CONCLUSIONS: Based on the low quality of exposure data and the difference in effect by study design, our findings indicate insufficient evidence for a link between night-shift work and breast cancer. Objective prospective exposure measurement is needed in future studies.